A methods engineering study on F.A.S. Development Corporation - Fuertez, Ma. Roneza (College of Engineering, 2001)
F.A.S. Development Corporation is the pioneer optical disc manufacturing company to operate in the country. This is one of the many reasons that the group had chosen the company to apply methods engineering. With the knowledge and proper practice, the group aims to improve the performance and gain of the company. The group documented the systems and procedures being applied and identified the problems that were encountered in the company through the use of an Ishikawa Diagram (cause and effect). Some of the problem areas identified were lack of policies governing proper attire for workers and untidiness in the printing area, inefficient layout for the plant and warehouse, and inefficiency of machines. The Ishikawa Diagram was employed in the analysis of the main problem, which is the rejection of CDs. In addressing these problem areas, the group generated one to three alternatives for each and evaluated the alternatives against the specific criteria of each problem area. The alternative chosen was based on the least consequences, a "GO" in all the must objectives, highest weighted score base on the want objectives and with the least cost estimated. The problem regarding the lack of policies is one of the reasons that point to the cause of rejection. This is mainly because, as from the interviews in the company, the transfer of dirt from the environment to the CDs during the process of production is one of the main reasons for the rejection of CDs. The group noticed that the workers do not have proper attire and some of the work areas are untidy. For the lack of proper attire, the group recommended that the management provide the workers with at least uniform per worker that are white in color as to catch attention if there are dusts in their clothing. For the problem regarding the untidiness of the work area specifically in the printing room, the group recommended that the management set some policies that should give responsibilities to the workers. For the attire, it will cost the management around P30,000 while the cost in the setting of responsibilities to the workers is very minimal. For the inefficiency of the plant layout, the group pointed out three problems, namely, the disorganized warehouse, inefficient production layout, and the inefficient utilization of space leading to messy work area. For the warehouse, the group designed a layout that will utilize the area better. The group also recommended the installation of steel shelves. This will cost the management around P350,000. For the production layout, a better layout was recommended . This new layout was designed so that the travel distance from one department to the other will be lesser and also the machines will be designated to proper places according to its order in the production process. For the messy work area, hanging shelves were recommended for the proper placement of materials and tools. Problems regarding the working conditions were also sighted. There is insufficient lighting and there is variation in the temperature around the work area. A new lighting system was proposed and the centralization of the air-conditioning system was recommended. An estimate of P1,000,000 will be spent if the centralization of the air conditioning system for the whole production area will be implemented. A new layout for the inspection sheet was proposed for improvement. There will almost be no cost to this, as only the format of the current inspection sheet will be changed. All chosen alternatives were recommended to the company along with the implementation plans and strategies that the group came up with. These plans and strategies will serve as guide in implementing the changes in the company brought about by the alternatives.